2019
DOI: 10.1002/hrdq.21347
|View full text |Cite
|
Sign up to set email alerts
|

Personal growth initiative as a predictor of psychological empowerment: The mediating role of job crafting

Abstract: Previous research has investigated the effects of socio‐organizational factors on psychological empowerment (PE), whereas only a limited number of studies have examined the influence of individual characteristics on PE. Drawing on self‐determination theory and social capital theory, this study hypothesized that personal growth initiative (PGI), a set of skills that facilitate self‐change, has an indirect and positive influence on PE as mediated by three types of job crafting. The results of a two‐wave longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
(167 reference statements)
4
18
0
Order By: Relevance
“…Hence, hypotheses H1b (CDàPE) and H2b (RRàPE) were supported, whilst hypothesis H3b (TDàPE) was not supported. Similar findings were confirmed by earlier researches also (Arefin et al, 2019;Matsuo, 2019;Moradi & Dashti, 2016). Also, the result confirmed that PE changed a greater level of EE (β = 0.70 and p < 0.001).…”
Section: Discussion and Practical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, hypotheses H1b (CDàPE) and H2b (RRàPE) were supported, whilst hypothesis H3b (TDàPE) was not supported. Similar findings were confirmed by earlier researches also (Arefin et al, 2019;Matsuo, 2019;Moradi & Dashti, 2016). Also, the result confirmed that PE changed a greater level of EE (β = 0.70 and p < 0.001).…”
Section: Discussion and Practical Implicationssupporting
confidence: 91%
“…Several studies found TMP as the key player to increase PE. Although there are different controversial results, many researchers empirically found that TMP (CD, RR, TD) positively and significantly influence PE (Arefin et al, 2019;Matsuo, 2019;Moradi & Dashti, 2016). In the direction of mediating effect of PE, the relationship between TMP and employee outcome has been documented in various research works, but contradictory outcomes have been found in the context of relationship amongst these variables.…”
Section: Linking Talent Management Practices Psychological Empowermen...mentioning
confidence: 99%
“…An example item is: “I am constantly trying to grow as a person.” The PGIS-II’s total score has demonstrated good internal consistency with a sample of 331 college students (α = .95) and was predictive of aspects of vocational identity development (Weigold et al, 2013). Additionally, PGI was found to predict job crafting in a longitudinal sample of 320 U.S. workers, and demonstrated adequate reliability (.90; Matsuo, 2019). In the current study, the total score demonstrated strong internal consistency (α = .93).…”
Section: Methodsmentioning
confidence: 98%
“…A higher personal growth initiative is linked to a better engagement at work and lower intention to leave (Srivastava & Bajpai, 2020). Individuals with personal growth initiative were more likely to employ job crafting, as an initiative to adjust one's task with one' preferences (Matsuo, 2019) which had a positive link with career commitment, moderated by a sense of calling (Chang, Rui, & Wu, 2021). Personal growth initiative also serves as the predictor of perceiving career calling in a cross-sectional study (Jurica, 2014).…”
Section: Personal Growth Initiative Career Commitment and Career Callingmentioning
confidence: 99%